If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 9x + 22 = 3x + 70 Reorder the terms: 22 + 9x = 3x + 70 Reorder the terms: 22 + 9x = 70 + 3x Solving 22 + 9x = 70 + 3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3x' to each side of the equation. 22 + 9x + -3x = 70 + 3x + -3x Combine like terms: 9x + -3x = 6x 22 + 6x = 70 + 3x + -3x Combine like terms: 3x + -3x = 0 22 + 6x = 70 + 0 22 + 6x = 70 Add '-22' to each side of the equation. 22 + -22 + 6x = 70 + -22 Combine like terms: 22 + -22 = 0 0 + 6x = 70 + -22 6x = 70 + -22 Combine like terms: 70 + -22 = 48 6x = 48 Divide each side by '6'. x = 8 Simplifying x = 8
| 18y+4=70 | | (9x^8yz^6)(6x^7z)= | | 4f-12=0 | | x-16=2x-14 | | 4x^4(-6x^5-7)= | | -x-3=x-19 | | 2x-15=x-21 | | 7x-14=-49 | | 6x+79=10x-9 | | 2x+9=-2x+29 | | 11=4-2x | | -0.3x+6=-0.5x+9 | | -0.3+6=-0.5+9 | | x+3=-2x-18 | | -3x+16=x+32 | | 2b^2-7b+6=0 | | (-4x^7)(6)= | | 5x-12=6x-18 | | 11x-15=4x-50 | | 2x+19=39 | | 5x+9=6x+13 | | -2x+17=-1 | | -x-1=-5x+27 | | 5x-14=-49 | | 3x-5=-2x-25 | | -x-1=-5x-25 | | -2x-3=-5x-9 | | 60x-180=5x^2 | | (2x^7)(9)= | | x^4+x^3-8x+8=0 | | (2y-5)(2y-5)= | | 4+14p-2=9p+72-5p |